Relationship between corneal confocal microscopy and markers of peripheral nerve structure and function in Type 2 diabetes. Issue 2 (6th April 2019) - Yan, A.; Issar, T.; Tummanapalli, S. S.; Markoulli, M.; Kwai, N. C. G.; Poynten, A. M.; Krishnan, A. V.
Abstract: Aims: To investigate changes in corneal nerve morphology in Type 2 diabetes and to establish relationships between in vivo corneal confocal microscopy and markers of peripheral nerve structure and function. Participants and methods: We recruited 57 participants with Type 2 diabetes and 26 healthy controls of similar age and sex distribution. We also recruited a disease control group of 54 participants with Type 1 diabetes. All participants were assessed for distal symmetrical polyneuropathy using the Total Neuropathy Score. In vivo corneal confocal microscopy was used to assess corneal nerve fibre length, corneal nerve fibre density, corneal nerve branch density and inferior whorl length. Peripheral nerve structure was assessed using median nerve ultrasonography. Large fibre function was assessed according to median nerve axonal excitability. Small fibre function was assessed using Sudoscan TM and the Survey of Autonomic Symptoms. Results: Corneal nerve fibre length, fibre density and branch density and inferior whorl length were significantly lower in individuals with Type 2 diabetes compared to controls ( P <0.001 for all). In the Type 2 diabetes cohort, correlations were observed between neuropathy severity and corneal nerve fibre density ( P =0.004), corneal nerve branch density ( P =0.003), corneal nerve fibre length ( P =0.002) and inferior whorl length ( P =0.01). Significant correlations were observed between corneal confocal outcomes and axonal excitability measurements. No association was found between corneal confocal microscopy and median nerve cross‐sectional area, Sudoscan measurements or the Survey of Autonomic Symptoms. Conclusions: This study demonstrated significant changes in corneal nerves in individuals with Type 2 diabetes. Reductions in corneal nerve measures correlated with increasing neuropathy severity. Associations were found between corneal confocal microscopy and markers of voltage‐gated potassium channel function. What's new?: In vivo corneal confocal microscopy is a validated diagnostic tool for diabetic peripheral neuropathy in Type 1 diabetes. Multicentre studies have recently demonstrated corneal nerve fibre length (CNFL) to be a valid endpoint for diabetic peripheral neuropathy in Type 2 diabetes. Changes in corneal nerve fibre density (CNFD) were apparent in participants with Type 2 diabetes without neuropathy. CNFL and CNFD were reduced with increasing neuropathy severity. A significant relationship was found between corneal nerves and physiological markers of peripheral nerve function. This study confirms the utility of in vivo corneal confocal microscopy in assessing neuropathy in Type 2 diabetes. Novel insights into the underlying pathophysiology of diabetic peripheral neuropathy in Type 2 diabetes were demonstrated by the significant relationship between corneal nerves and axonal excitability outcomes.